2019
DOI: 10.14744/tjtes.2019.08433
|View full text |Cite
|
Sign up to set email alerts
|

Fat Embolism Syndrome After Gluteal Augmentation with Hyaluronic Acid: A Case Report

Abstract: Fat embolism syndrome (FES) occurs classically characterized by the combination of acute respiratory failure, neurologic abnormalities, and a petechial rash. Forty-six-year-old female presented to our emergency department with agitation, altered mental status, and drowsiness. We learned that the patient had received a hyaluronic acid (HA) injection into her buttocks at a beauty center a few hours before her admission. She had no skin findings, but she was hypoxemic. She had lung computed tomography (CT) findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Alternatively, a paradoxical embolism whereby the embolus passes from a patent foramen ovale and enters the arterial circulation, or a microembolism where small emboli pass through the pulmonary artery into the pulmonary and systemic circulation are possible mechanisms. This patient's CECT thorax findings with bilateral ground-glass opacification have also previously been reported in other similar cases of fat embolism syndrome [ 6 ].…”
Section: Discussionsupporting
confidence: 82%
“…Alternatively, a paradoxical embolism whereby the embolus passes from a patent foramen ovale and enters the arterial circulation, or a microembolism where small emboli pass through the pulmonary artery into the pulmonary and systemic circulation are possible mechanisms. This patient's CECT thorax findings with bilateral ground-glass opacification have also previously been reported in other similar cases of fat embolism syndrome [ 6 ].…”
Section: Discussionsupporting
confidence: 82%
“…However, such complications are more frequently mentioned in the context of facial treatments. [22][23][24] The use of HA gel injections for gluteal augmentation was investigated by two prospective studies, 13,14 which showed that this is a safe and effective treatment for temporary aesthetic gluteal augmentation. Camenisch et al 12 treated eight participants with a mean of 163 mL of HA per gluteus, reporting 56%, 36%, and 24% of gel remaining after 6, 12, and 24 months, respectively, located primarily in the subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%
“…However, such complications are more frequently mentioned in the context of facial treatments. 22 24 …”
Section: Discussionmentioning
confidence: 99%
“…We performed a filtered search for “within 5 years” and “case report” using the keywords “cerebral fat embolism” and “MRI” in a PubMed search. Of 42 cases of cerebral fat embolism included in 39 papers, 3–41 we analyzed 33 cases 3–17,19–26,28–30,32,34,37,39,40 after excluding the following: (1) cases not available ( n = 2), 27,35 (2) not a case report ( n = 1), 33 (3) not in English ( n = 1), 18 (4) not cerebral fat embolism ( n = 3), 36,38,41 (5) diagnosis obtained by CT instead of MRI ( n = 1), 32 and (6) MRI contraindicated due to a magnetic implant ( n = 1) 31 . Of the 33 cases, SWI of the brain was acquired in 10 cases 4,5,10,12,17,25,34,36,37,41 …”
Section: Discussionmentioning
confidence: 99%